Identification of Streptomyces sp-MWS1 Producing Antibacterial Compounds - retnowati, Wiwin (Indonesian Journal of Tropical and Infectious Disease, 2010)
An actinomycete, designated Streptomyces sp-MWS1, was isolated from mangrove ecosystem soil in the eastern coast of Surabaya.  This organism was capable of producing a series of antibiotics that strongly inhibit the growth of Gram-positive and Gram-negative bacteria. Furthermore, culture morphological and physiological characteristics of the isolated strain, Streptomyces sp-MWS1 were compared to other reference strains belong to Streptomyces species. The analysis of nucleotide sequence of the 16S rDNA indicated similarity binary 98% with Streptomyces species.